Pengaruh Penggunaan Media Gambar Seri Terhadap Kemampuan Kreativitas Siswa Sekolah Dasar - Putri Bulqhis Anindhita; Supriyadi (Jurnal Ilmiah Global Education, 2026)
Creativity is an important ability that needs to be developed since elementary education, especially thorugh fine arts learning. However, thr low creativity of students in drawing is often caused by the limited avaibility of attractive visual media and the inability to stimulate imagination. Serial drawing media is seen as an alternative learning method that can help students develop ideas coherently and creatively. This study aims to analyze the effect of using serial drawing media on the creatibity abilities of elementary school students. The research subjects were 15 elementary school student with a saturated sampling technique. The research instrument was a worsheet based on drawing creativity indicators. Data analysis was carried out throgh the Shapiro- Wilk normality test, the Wicoxon Signed Rank Tests, and the calculation of effect size using Partial Eta Squered. The results of the study showed a significant increase in students drawing creativity after using serial drawing media. The significance value of 0.001 (<0,05) and Partial Eta Squered of 0,935 indicate a very large influence, so that serial drawing media is affective in increasing the creativity abilities of elemnetary school students.